HUBUNGAN POLA MAKAN, PENGETAHUAN GIZI SEIMBANG DAN SOSIAL BUDAYA DENGAN STATUS GIZI CALON PENGANTIN DI KUA KECAMATAN PANCORAN MAS KOTA DEPOK TAHUN 2022 - Dwi Dini Krisdayani (2022)
Prospective married couple are the main focus in efforts to improve nutrition. This is related to the importance of nutritional status before pregnancy and labor. The purpose of this study is to determine relationship between diet, nutritional knowledge and socio-culture with prospective married couple nutritional status in KUA Pancoran Mas. This study used cross-sectional method with consecutive sampling technique, conducted on 136 respondents. Univariate analysis showed that majority of respondent have normal nutritional status (63.2%), eat variety of foods (76.5%), appropiate eating frequency (72.1%), have sufficient nutritional knowledge (57.4 %), no dietary restrictions (59.6%) and not believe in myths (52.9%). The results of chi-square test showed that there was relationship between food diversity (p value=0.047) and nutritional knowledge (p value=0.020) with nutritional status, and there was no relationship between eating frequency (p value=0.834), dietary restrictions (p value=0.178) and myths (p value=0.470) with nutritional status. The conclusion is that food diversity and nutritional knowledge are related to prospective married couple nutritional status, while eating frequency, dietary restrictions and myths are not related to prospective married couple nutritional status. Prospective married couple should pay more attention to their nutritional status by checking their health and increasing their nutrition knowledge by seeking information.